Analisis flypaper effect berdasarkan kemampuan keuangan daerah (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
This study aimed to analyzed the local financial capacity Kutai Kartanegara regency suspected of having flypaper effect. Types of the data from this research is quantitative. The types of the data in this research is in the form of time series data reports on realization of local revenue (PAD), equalization funds, regional expenditures and the amount of revenue Kutai Kartanegara Regency using quantitative analysis methods. Using the methods of analysis of financial index capability ratio (ICR) and analysis of the degree of fiscal decentralization. The results of the analysis in this research shows that the first analysis of the index calculation financial capability ratio Kutai Kartanegara Regency in the last three years shows the indicator is very low and can be said to experience the phenomenon flypaper effect and the second analysis, the calculation of the degree of fiscal decentralization Kutai Kartanegara Regency show the indicator is very less, This implies Kutai Kartanegara Regency government is still unable to finance its own expenses and still dependent on central government funding.